2001
DOI: 10.1002/1099-0682(200112)2001:12<3113::aid-ejic3113>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced C−H Activation and Catalytic Carbonylation of Benzene − New Features of a Tris(pyrazolyl)methanesulfonato (Tpms) Rhodium(I) Complex

Abstract: Irradiation of [(Tpms)Rh(CO)(PMe3)] (1) in benzene or [D6]benzene affords the rhodium(III) compounds [(Tpms)Rh(H)(C6H5)(PMe3)] (2) and [(Tpms)Rh(D)(C6D5)(PMe3)] (2‐d6) respectively. The kH/kD ratio for the formation of 2 and 2‐d6 was found to be 1.1. The complexes 2 and 2‐d6 are stable in protic solvents. When a solution of 1 in benzene is irradiated under carbon monoxide pressure, benzaldehyde is formed catalytically with turnover numbers of up to 20. The formation of 2 and [(Tpms)Rh(H)(COC6H5)(PMe3)] (4) und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 32 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…The postulated pentacoordinate intermediate (Scheme ) would undergo migratory insertion, resulting in the square planar complex 5 . CO loss, evident by the formation of complex 6 , may also be expected to occur from the suggested pentacoordinate rhodium species under the reaction conditions. , The main mechanistic difference in the photocarbonylation of benzene by complex 3 , versus that of the Vaska-type rhodium complexes, ,,, is that benzene activation by the Rh­(I) takes place by metal–ligand cooperation, and hence the product is a Rh­(I) benzoyl complex (rather than Rh­(III)), with no overall change in the metal oxidation state.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The postulated pentacoordinate intermediate (Scheme ) would undergo migratory insertion, resulting in the square planar complex 5 . CO loss, evident by the formation of complex 6 , may also be expected to occur from the suggested pentacoordinate rhodium species under the reaction conditions. , The main mechanistic difference in the photocarbonylation of benzene by complex 3 , versus that of the Vaska-type rhodium complexes, ,,, is that benzene activation by the Rh­(I) takes place by metal–ligand cooperation, and hence the product is a Rh­(I) benzoyl complex (rather than Rh­(III)), with no overall change in the metal oxidation state.…”
Section: Resultsmentioning
confidence: 98%
“…Although a radical mechanism cannot be excluded for the photocarbonylation reaction, , and while early studies had suggested the possibility of a dissociative mechanism (ligand or CO extrusion) to lead to C–H activation; exhaustive mechanistic research, conducted by Goldman, and Field on rhodium-catalyzed photocarbonylation of benzene suggests that it may proceed by an associative mechanism, whereby UV irradiation excites the rhodium carbonyl complex 3 , enabling C–H activation of benzene. In the case of the PNP pincer complex 3 , C–H activation by MLC leads to re-aromatization of the pincer ligand, which may serve as a driving force for this reaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As reported in the literature, the [Rh(Tpms)(CO) 2 ] complex catalyses the hydroformylation of 1-hexene at 60°C in acetone, but its instability in water has prevented any possible investigation in aqueous media [6]. On the other hand, [Rh(Tpms)(CO)(PMe 3 )] has been shown to act as a catalyst for both the hydroformylation of 1-hexene and the carbonylation of benzene [6,7], although the study was also carried out only in non-aqueous solvents for stability reasons. Among the different [Rh(Tpms)(CO)(PR 3 )] complexes described in the literature [1], only the compound [Rh(Tpms)(CO)(PPh 2 PhSO 3 K)] was found to be well soluble in aqueous media, its stability in water, however, being limited to the short pH range of 3-4. In order to overcome these stability problems in aqueous phase, we wondered whether the use of the chemically stable and watersoluble 1,3,5-triaza-7-phosphaadamantane (PTA) ligand instead of the previously reported phosphines [1] could confer a greater stability to the Rh I system.…”
Section: Introductionmentioning
confidence: 99%